Design and structural analysis of a control moment gyroscope (CMG) actuator for cubesats - Gaude, Alexis; Lappas, Vaios (MDPI, 2020)
Following a global trend towards miniaturization, the population of nano- and micro-satellite continues to increase. CubeSats are standardized small size satellites based on 10 × 10 × 10 cm cube modules (1U) and are becoming sophisticated platforms despite their very small size. This paper details the design and the structural analysis of a Control Moment Gyroscope (CMG) actuator for agile CubeSats with a physical size up to 12U, which require high torque actuators. CMGs have inherited torque amplification capabilities and the recent advances in motor miniaturization make them ideal candidates for small satellite missions with slew rate requirements. The system’s requirements are derived based on conceptual agility requirements for an agile (highly maneuverable) CubeSat which needs to achieve a 90° maneuver in 90 s. With specific cost, mass and volume requirements, the proposed CMG design is based on some of the smallest available off-the-shelf electric motors and uses a light aluminum casing design. The proposed design uses stepper motors for the gimbal mechanism as a low cost, compact and low power solution, contributing to an overall low mass of the full CMG cluster. Static and dynamic analyses were performed to assess the mechanical integrity of the system for launch loads. Apart from a necessary custom control electronic board, the complete mechanical assembly has been designed including electrical hardware. Analyses demonstrate that the overall stress levels acting on the system are manageable by the CMG design. Bolted joints are critical and should be studied independently as the chosen model created singularities around these areas. Each individual CMG of the designed pyramidal cluster is shown to weigh about 35 g. Using the proposed CMG design with a customized avionics board, the complete CMG system is shown to weigh 250 g and occupies slightly more than ½U volume for a CubeSat, indicating the feasibility of CMGs for agile CubeSats
Keywords: finite element analysis; control moment gyroscope; attitude control; CubeSat